Pretreatment of Palm Kernel Cake by Enzyme-Bacteria and Its Effects on Growth Performance in Broilers - Yue Liu; Ying Liu; Yunhe Cao; Chunlin Wang (Animals)
This study aimed to improve palm kernel cake by reducing anti-nutritional factors with enzymes and enhancing its nutritional value through microbial fermentation. It also examined the effects of these treatments on palm kernel cake in broiler chicken diets. Palm kernel cake was hydrolyzed using xylanase and mannanase under various conditions. Co-fermentation with Lactobacillus plantarum QZSL and Saccharomyces boulardii mafic-1701 was assessed under different parameters. In the animal experiment, 350 male Cobb broiler chicks were divided into seven groups: a control group provided a corn-soybean meal diet, and groups provided diets containing 10% and 20% palm kernel cake, enzyme-hydrolyzed palm kernel cake, and bacteria-enzyme co-fermented palm kernel cake. Optimal conditions for enzymatic hydrolysis of palm kernel cake are 55 °C, pH 3.0, and a 1:2.5 feed-to-water ratio. Adding 0.1 g xylanase and 1.0 g mannanase to 10 g palm kernel cake for 12 h increased reduced sugar content to 139.33 mg/g and reduced neutral detergent fiber to 43.92%. For solid-state fermentation with Lactobacillus plantarum QZSL and Saccharomyces boulardii mafic-1701, optimal conditions are 37 °C, 5% inoculation, 20% moisture, 3 days fermentation, and a 7:3 bacterial ratio. Animal experiments showed significant improvements in broilers’ growth, nutrient digestibility, antioxidant capacity, immune function, and intestinal health. Enzyme-bacteria co-fermentation of palm kernel cake boosts its nutritional value and enhances broiler intestinal health.